Assessment of the Neuroprotective Effects of Lavandula angustifolia Extract on the Contusive Model of Spinal Cord Injury in Wistar Rats - Kaka, Gholamreza; Yaghoobi, Kayvan; Davoodi, Shaghayegh; Hosseini, Seyed R.; Sadraie, Seyed H.; Mansouri, Korosh (Frontiers in Neuroscience, 2016)
Introduction Spinal cord injury (SCI) involves a primary trauma and secondary cellular processes that can lead to severe damage to the nervous system, resulting in long-term spinal deficits. At the cellular level, SCI causes astrogliosis, of which glial fibrillary acidic protein (GFAP) is a major index. Objective The aim of this study was to investigate the neuroprotective effects of Lavandula angustifolia (Lav) on the repair of spinal cord injuries in Wistar rats. Materials and Methods Forty-five female rats were randomly divided into six groups of seven rats each: the intact, sham, control (SCI), Lav 100, Lav 200, and Lav 400 groups. Every week after SCI onset, all animals were evaluated for behavior outcomes by the Basso, Beattie, and Bresnahan (BBB) score. H&E staining was performed to examine the lesions post-injury. GFAP expression was assessed for astrogliosis. Somatosensory evoked potential (SEP) testing was performed to detect the recovery of neural conduction. Results BBB scores were signiﬁcantly increased and delayed responses on sensory tests were signiﬁcantly decreased in the Lav 200 and Lav 400 groups compared to the control group. The greatest decrease of GFAP was evident in the Lav 200 and Lav 400 groups. EMG results showed significant improvement in the hindlimbs in the Lav 200 and Lav 400 groups compared to the control group. Cavity areas significantly decreased and the number of ventral motor neurons significantly increased in the Lav 200 and Lav 400 groups. Conclusion Lav at doses of 200 mg/kg and 400 mg/kg can promote structural and functional recovery after SCI. The neuroprotective effects of L. angustifolia can lead to improvement in the contusive model of spinal cord injury in Wistar rats. Keywords Spinal cord injury (SCI); Lavandula angustifolia; neuroprotection; Basso, Beattie, and Bresnahan (BBB); glial fibrillary acidic protein (GFAP); somatosensory evoked potential (SEP)